Les éléments territoriaux naturels mobiles subissant les conséquences du changement climatique : esquisse d’un régime de droit international en devenir - Jochen Sohnle (VertigO)
This paper is looking for a comprehensive international legal regime applying to mobile natural elements of territory (such as living species and water resources) in the context of climate change. In a first step, these elements have to be defined in relation to the existing legal theories on state territory. Even if there are some conceptual difficulties to face mobility of natural elements following a traditional international law approach, it is indeed possible to gather them into a homogenous legal category. This allows, in a second step, to establish procedural and substantive principles applicable for these elements in international law.